Immune checkpoint inhibitors and elderly people: A review. (September 2017) - Daste, Amaury; Domblides, Charlotte; Gross-goupil, Marine; Chakiba, Camille; Quivy, Amandine; Cochin, Valérie; de Mones, Erwan; Larmonier, Nicolas; Soubeyran, Pierre; Ravaud, Alain
Abstract: Immune checkpoint inhibitors, including targeting programmed cell death 1, programmed cell death ligand 1, and cytotoxic T lymphocyte antigen 4 pathways, are a new type of cancer treatment. This approach of targeting the immune system has demonstrated dramatic efficacy for several cancers, and various drugs have been approved by health authorities and are used in clinical practice. Elderly patients (≥65 years) represent most of the cancers diagnosed and deaths by age group, with an increase expected over the next decade. However, this subgroup of patients is under-represented in clinical trials. Ageing is also associated with a decrease in the effectiveness of the immune system and in alterations to it. Few specific trials have been carried out for immunotherapy in elderly people, with most patients considered to be fit. In this review, we discuss the impact of ageing and immunosenescence on immune system functions, and we assess the safety and efficacy of immune checkpoint inhibitors in elderly patients, principally from the data of pivotal clinical trials with subgroup analysis. Tolerance in elderly patients seems similar to younger people, but efficacy seems different between younger and elderly patients according to the type of cancer, some showing no difference and others less efficacy in the elderly subgroup. However, the numbers in elderly groups are small and more investigation is needed, with specific clinical trials for elderly cancer patients. Highlights: Elderly patients (≥65 years) represent most of the cancer diagnoses and deaths by age group. Safety and efficacy of immune check point inhibitors in elderly patients are extracted from data of pivotal clinical trials. Ageing is associated with a decrease in the effectiveness of the immune system and remains a risk factor for auto-immunity. We analysed the major clinical trial for immunotherapy for the subgroups of elderly people.